IMPLEMENTASI PENGALAMAN BELAJAR 3D SISWA KELAS VII SMPN 1 WAGIR MELALUI PEMANFAATAN APLIKASI AUGMENTED REALITY "ARPI" PADA MATERI ZAMAN PRA AKSARA - Rasyid, Hamidi; Fudla, Maziyyatul; Fahri, Amar Ma’ruf; Jamhariroh, Ulil; Putri, Noviyana; Anjarwati, Along; Ainiyah, Siti Mahfirotus (Jurnal Edukasi Pengabdian Masyarakat, 2025)
The Community Service activity aims to equip students and teachers to understand learning when using augmented reality tools, this shows that augmented reality (AR) has great potential as an engaging educational tool for social studies at SMPN 1 Wagir. Despite having some technical limitations, the benefits of AR in increasing student engagement and understanding are very significant. It is hoped that the results of this activity will be a valuable reference for schools and related stakeholders to advance infrastructure and provide teacher training, thereby maximizing the integration of AR in the educational environment.